2022
DOI: 10.11648/j.ijgg.20221001.11
|View full text |Cite
|
Sign up to set email alerts
|

Milk Productive Performances of Pure Jersey Dairy Cattle at Adea-Berga Dairy Research Center, Central Highland of Ethiopia

Abstract: Performance evaluations for economically important milk production traits are the bases for genetic evaluation, planning breeding program and selection for dairy cows. This study was intended to evaluate milk production traits of pure Jersey dairy cows at Adea-Berga Dairy research center. The data collected from 1986 to 2019 from a herd maintained at Adea-Berga dairy research center was used to estimate milk production traits (lactation milk yield (LMY), daily milk yield (DMY) and lactation length (LL)). A gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…The year of calving had a significant effect on all the studied milk production traits except lactose (P<0.05). Tadesse and Dessie (2003), Beneberu et al (2020), andGetahun et al (2020) reported that the calving year significantly affected daily milk yield in Holstein Friesians and their crosses in Ethiopia; this is similar to this study. However, Verma et al (2016) found that the calving year did not affect test-day milk yield.…”
Section: Effect Of Calving Yearsupporting
confidence: 88%
“…The year of calving had a significant effect on all the studied milk production traits except lactose (P<0.05). Tadesse and Dessie (2003), Beneberu et al (2020), andGetahun et al (2020) reported that the calving year significantly affected daily milk yield in Holstein Friesians and their crosses in Ethiopia; this is similar to this study. However, Verma et al (2016) found that the calving year did not affect test-day milk yield.…”
Section: Effect Of Calving Yearsupporting
confidence: 88%
“…The non-significant difference in lactation length from the second to sixth parities indicates the stability of lactations and milk yield (Table 2). Similar results were also obtained by Kumar et al (2016) Frieswal cows in the northern zone of India and Beneberu et al (2020) in pure Jersey cattle. W hereas, the nonsignificant effect of parity was reported by Dongre et al (2017) in Deoni cattle of Marathwada region and Rokade et al (2021) in Phule Triveni cattle.…”
Section: Effect Of Non Genetic Factors and Sire On Lactation Length I...supporting
confidence: 83%
“…The variation in lactation length observed during different periods might be due to the level of management practices introduced from one year to another and the variations caused due to the environmental factors like fluctuations in temperature and humidity and also due to some genetic factors like herd genetic levels, changes in the age of the animals etc. The significant effect of the period of calving on lactation length was found by Chopade et al (2002) in crossbred cattle, Das et al (2011) in crossbred dairy cows and Beneberu et al (2020) in pure Jersey cattle in Central Highland Ethiopia. Highly significant effect of period of calving on first lactation length was observed by Eid (2012) in Friesian cattle, Hussain et al (2015) in Tharparkar cattle.…”
Section: Effect Of Non Genetic Factors and Sire On Lactation Length I...mentioning
confidence: 78%